Midostaurin potentiates rituximab antitumor activity in Burkitt's lymphoma by inducing apoptosis. Issue 1 (2018) - Ge, Xiaowen; Chen, Jianfeng; Li, Ling; Ding, Peipei; Wang, Qi; Zhang, Wei; Li, Luying; Lv, Xinyue; Zhou, Danlei; Jiang, Zhengzeng; Zeng, Haiying; Xu, Yifan; et al.
Abstract An intensive short-term chemotherapy regimen has substantially prolonged the overall survival of Burkitt's lymphoma (BL) patients, which has been further improved by addition of rituximab. However, the inevitable development of resistance to rituximab and the toxicity of chemotherapy remain obstacles. We first prepared two BL cell lines resistant to rituximab-mediated CDC. Using a phosphorylation antibody microarray, we revealed that PI3K/AKT pathway contained the most phosphorylated proteins/hits, while apoptosis pathway that may be regulated by PKC displayed the greatest fold enrichment in the resistant cells. The PI3K/AKT inhibitor IPI-145 failed to reverse the resistance. In contrast, the pan-PKC inhibitor midostaurin exhibited potent antitumor activity in both original and resistant cells, alone or in combination with rituximab. Notably, midostaurin promoted apoptosis by reducing the phosphorylation of PKC and consequently of downstream Bad, Bcl-2 and NF-κB. Therefore, midostaurin improved rituximab activity by supplementing pro-apoptotic effects. In vivo, midostaurin alone powerfully prolonged the survival of mice bearing the resistant BL cells compared to rituximab alone treatments. Addition of midostaurin to rituximab led to dramatically improved survival compared to rituximab but not midostaurin monotherapy. Our findings call for further evaluation of midostaurin alone or in combination with rituximab in treating resistant BL in particular.